Characteristics of lower extremity work during the impact phase of jumping and weightlifting - Moolyk, A. N.; Carey, J. P.; Chiu, L. Z. F. (The Journal of Strength and Conditioning Research, 2013)
Jumping and weightlifting tasks involve impact phases, where work is performed by the lower extremity to absorb energies present at contact. This study compared the lower extremity kinematic and kinetic strategies to absorb energy during the impact phase of jumping and weightlifting activities. Ten women experienced in jumping and weightlifting performed 4 tasks (landing from a jump, drop landing, clean, and power clean) in a motion analysis laboratory. Work performed at the hip, knee, and ankle were calculated during the landing and receiving phases of jumping and weightlifting tasks, respectively. Additionally, segment and joint kinematics and net joint moments were determined. The most lower extremity work was performed in the clean and drop landing, followed by landing from a jump, and the least work was performed in the power clean (p < 0.05). For all tasks, work performed by the knee extensors was the greatest contributor to lower extremity work. Knee extensor net joint moment was greater in the power clean than jump and drop landings, and greater in the clean than all other tasks (p < 0.05). Knee flexion angle was not different between the power clean and jump landing (p > 0.05) but greater in the drop landing and clean (p < 0.05). A common characteristic of the impact phase of jumping and weightlifting tasks is a large contribution of knee extensor work. Further, the correspondence in kinematics between impact phases of jumping and weightlifting tasks suggests that similar muscular strategies are used to perform both types of activities. Weightlifting tasks, particularly the clean, may be important exercises to develop the muscular strength required for impact actions due to their large knee extensor net joint moments.